Innovation and Technology Adoption in Central America - Andrés Rodríguez-Clare (Inter-American Development Bank, Research Department, 2005)
In spite of deep structural reforms, Central American countries have failed to experience rapid and stable growth in recent years. This paper explores whether and to what extent we can consider lack of innovation and technology adoption as a main reason for this disappointing experience. The paper starts by documenting that technology adoption and innovation are indeed very low, and then turns to a more qualitative and eclectic analysis drawing on interviews and case studies to try to understand the reasons for this. Four hypotheses are explored: weak intellectual property rights, low competition, lack of finance and low levels of education. The conclusion that emerges is that the last two of these four hypotheses may be especially relevant for the region. The paper concludes with several policy recommendations.
Keywords: 330; Innovation; Technologiewahl; Mittelamerika; Costa Rica